ENVIRONMENTAL POLLUTION - Arvita Adellia Saputri; Salim; Ruth Ambarsari (Akademi Seni dan Desain Indonesia Surakarta, 2022)
Final project planning aims to create a party fashion design that combines the source of ideas and fashion style chosen. The source of ideas from the final project design is Enviromental Pollution. Environmental Pollution poured into clothing with a pattern application patchwork dan tie dyed techbiques as fashion motifs, meanwhile fashion style is avant garde. The type of clothing chosen is eveing dress. The materials used in the final prpject design are linen, tulle, and silk catton fabric for tie dyed. The colors of the material in the final project design follow the color of the source of ide, namely blue Keywords environmental pollution